Augmented Enterocyte Damage During Candida albicans and Proteus mirabilis Coinfection - Niemiec, Maria Joanna; Kapitan, Mario; Himmel, Maximilian; Döll, Kristina; Krüger, Thomas; Köllner, Tobias G.; Auge, Isabel; Kage, Franziska; Alteri, Christopher J.; Mobley, Harry L.T.; Monsen, Tor; Linde, Susanne; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
The human gut acts as the main reservoir of microbes and a relevant source of life-threatening infec-tions, especially in immunocompromised patients. There, the opportunistic fungal pathogen Candida albicans adapts to the host environment and additionally interacts with residing bacteria. We investigated fungal-bacterial interactions by coinfecting enterocytes with the yeast Candida albi-cans and the Gram-negative bacterium Proteus mirabilis resulting in enhanced host cell damage. This synergistic effect was conserved across different P. mirabilis isolates and occurred also with non-albicans Candida species and C. albicans mutants defective in filamentation or candidalysin produc-tion. Using bacterial deletion mutants, we identified the P. mirabilis hemolysin HpmA to be the key effector for host cell destruction. Spatially separated coinfections demonstrated that synergism be-tween Candida and Proteus is induced by contact, but also by soluble factors. Specifically, we identi-fied Candida-mediated glucose consumption and farnesol production as potential triggers for Proteus virulence. In summary, our study demonstrates that coinfection of enterocytes with C. albicans and P. mirabilis can result in increased host cell damage which is mediated by bacterial virulence factors as a result of fungal niche modification via nutrient consumption and production of soluble factors. This supports the notion that certain fungal-bacterial combinations have the potential to result in enhanced virulence in niches such as the gut and might therefore promote translocation and dissemination.